2013
DOI: 10.3382/ps.2012-02422
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corn replacement by sorghum in broiler diets on performance and intestinal mucosa integrity

Abstract: The effect of replacing corn with low-tannin sorghum on broiler performance, carcass yield, integrity of mucosa of small intestine segments, and activity of membrane enzymes of the jejunum is investigated. A total of 594 male Cobb-500 broiler chicks were randomly assigned to 3 dietary treatments: 100% corn (control), 50% corn replacement with low-tannin sorghum (low sorghum), and 100% corn replacement with low-tannin sorghum (high sorghum). Body weight gain, feed consumption, feed conversion, and carcass yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
36
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 23 publications
10
36
1
11
Order By: Relevance
“…The results of our study are consistent with previous reports of others (Garcia et al, 2013;Torres et al, 2013;Stringhini et al, 2009;Rocha et al, 2008;Santos et al, 2006) who did not find any differences in feed intake, weight gain or feed conversion when evaluating the growth performance of broilers fed sorghum as partial corn replacement in diets. Zarghi and Golian, (2009) also, revealed that 50% corn replacement with triticale had no negative effect on broiler growth performance.…”
Section: Growth Performancesupporting
confidence: 93%
“…The results of our study are consistent with previous reports of others (Garcia et al, 2013;Torres et al, 2013;Stringhini et al, 2009;Rocha et al, 2008;Santos et al, 2006) who did not find any differences in feed intake, weight gain or feed conversion when evaluating the growth performance of broilers fed sorghum as partial corn replacement in diets. Zarghi and Golian, (2009) also, revealed that 50% corn replacement with triticale had no negative effect on broiler growth performance.…”
Section: Growth Performancesupporting
confidence: 93%
“…This effect was attributed to the negative effects of sorghum tannins. Torres et al (2013) reported that the replacement of 100% dietary corn with low-tannin sorghum had negative effects on that performance and intestinal mucosa of broiler chickens. Dei et al (2008) stated that broilers fed diet containing shea nut meal (a high-tannin feed ingredient) had lower performance than those fed the control diet.…”
Section: Resultsmentioning
confidence: 99%
“…Sorghum is an interesting energy ingredient in poultry diets due to its similar nutritional composition to corn (Leeson and Summers, 2005). Previous study reported that the total or partial replacement of corn with sorghum is a viable option from the first week of life (Torres et al, 2013). Some studies showed that sorghumbased diets impair broiler performance (Jacobs and Parsons, 2013), or had a negative effect on the intestinal mucosa (Torres et al, 2013), whereas others indicated similar performance as the control diet (Campos et al, 2007;Bozutti, 2009;Fernandes et al, 2013;Tandiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that the total or partial replacement of corn with sorghum is a viable option from the first week of life (Torres et al, 2013). Some studies showed that sorghumbased diets impair broiler performance (Jacobs and Parsons, 2013), or had a negative effect on the intestinal mucosa (Torres et al, 2013), whereas others indicated similar performance as the control diet (Campos et al, 2007;Bozutti, 2009;Fernandes et al, 2013;Tandiang et al, 2014). However, there is some resistance to this replacement, especially in the starter phase, due to the possible presence of antinutritional factors in sorghum grain, such as condensed tannin, which affect broiler performance (García et al, 2013; Tandiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%